Isolation and Structure Elucidation of Soulatro Coumarin From Stem Bark of Calophyllum soulattri Burm F and In Vivo Antiplasmodial Activity by Using Mice Infected by Plasmodium berghei - Abbas, Jamilah; Darmawan, Achmad; Syafruddin, . (Indonesian Journal of Cancer Chemoprevention, 2011)
The soulatro coumarin compound was isolated and elucidated from the stem bark of Calophyllum soulattri Burm F, the samples were collected from Jayapura Papua Irian Island inÃÂ  Indonesia.ÃÂ  IsolationÃÂ  processÃÂ  wasÃÂ  doneÃÂ  byÃÂ  macerationÃÂ  atÃÂ  roomÃÂ  temperatureÃÂ  inÃÂ  methanol, thanÃÂ  partitionedÃÂ  inÃÂ  aÃÂ  mixtureÃÂ  ofÃÂ  nÃÂ  hexane-waterÃÂ  (1:1),ÃÂ  followedÃÂ  byÃÂ  dichloromethane-water (1:1)ÃÂ ÃÂ ÃÂ  andÃÂ  ethylÃÂ  acetate-waterÃÂ  (1:1).ÃÂ  AÃÂ  portionÃÂ  ofÃÂ  ethylÃÂ  acetateÃÂ  extractÃÂ  wasÃÂ  subjectedÃÂ  to column chromatography over silica gel packed and eluted with n-hexane a gradient of ethyl acetate to 100% followed by CHCl3ÃÂ  in MeOH (20:1, 10 :1, 5:1, 1:1). FractionÃÂ  B (CHCl3 in MeOH 20:1) was subjected to column chromatographyÃÂ  over silica gel 300 meshÃÂ  and eluted withÃÂ  EtOAc-MeOHÃÂ  mixturesÃÂ  ofÃÂ  increasingÃÂ  polarity.ÃÂ  FactionÃÂ  withÃÂ  theÃÂ  sameÃÂ  RfÃÂ  valeusÃÂ  were combinedÃÂ  andÃÂ  elutedÃÂ  withÃÂ  EtOAc-MeOHÃÂ ÃÂ ÃÂ  (19:1)ÃÂ  showedÃÂ  oneÃÂ  spotÃÂ  onÃÂ  TLC.ÃÂ  TheyÃÂ  were combinedÃÂ  andÃÂ  evaporatedÃÂ  toÃÂ  yieldÃÂ  aÃÂ  solidÃÂ  thanÃÂ  wasÃÂ  recrystallizedÃÂ  inÃÂ  mixtureÃÂ  ofÃÂ  CH2Cl2-methanolÃÂ  toÃÂ  giveÃÂ  soulatroÃÂ  coumarinÃÂ  compound.ÃÂ  TheÃÂ  structureÃÂ  wasÃÂ  determinatedÃÂ  by spectroscopic analysis, in particular by 1D and 2D NMR techniques, from these spectra data conclutionÃÂ  thatÃÂ  compoundÃÂ  isÃÂ  soulatroÃÂ  coumarin.ÃÂ  AntimalarialÃÂ  assayÃÂ  wasÃÂ  testedÃÂ  against Plasmodium berghei parasite as in vivo using 18 mices rodent wich was infected byÃÂ  Plasmodium bergheiÃÂ  parasite.ÃÂ  TheÃÂ  soulatroÃÂ  coumarinÃÂ ÃÂ ÃÂ  showedÃÂ  activityÃÂ  againstÃÂ  P.ÃÂ  bergheiÃÂ  withÃÂ  dosage 0.0005867ÃÂ  mM/1ÃÂ  kgÃÂ  bodyÃÂ  weightÃÂ  ;ÃÂ  0.005867ÃÂ  mM/1ÃÂ  kgÃÂ  bw;ÃÂ  0.05867ÃÂ  mM/1ÃÂ  kgÃÂ  bw;ÃÂ  0.5867 mM/1ÃÂ  kgÃÂ  bwÃÂ  5.867ÃÂ  mM/1ÃÂ  kgÃÂ  bwÃÂ  andÃÂ  58.67ÃÂ  mM/1ÃÂ  kgÃÂ  bwÃÂ  couldÃÂ  inhibiteÃÂ  growthÃÂ  rateÃÂ  of parasite = 57.32%; 63.37%; 43.02%; 53.49%; 47.67% respectively. ÃÂ  Keywords : Antiplasmodial activity, coumarin, Calophyllum soulattri Burm. F, in vivo,ÃÂ  Chloroquine, Plasmodium berghei.